Enhanced Oil Recovery : Resonance Macro- and Micro-Mechanics of Petroleum Reservoirs /: Resonance Macro- and Micro-Mechanics of Petroleum Reservoirs. (2016) - Ganiev, O. R; Ganiev, R. F; Ukrainsky, L. E
No abstract available